Comparison of different rate constant expressions for the prediction of charge and energy transport in oligoacenes. (1st July 2016) - Stehr, V.; Fink, R. F.; Tafipolski, M.; Deibel, C.; Engels, B.
Abstract : Charge and exciton transport in organic semiconductors is crucial for a variety of optoelectronic applications. The prediction of the material‐dependent exciton diffusion length and the charge carrier mobility is a prerequisite for tailoring new materials for organic electronics. At room temperature often a hopping process can be assumed. In this work, three hopping models based on Fermi's Golden rule but with different levels of approximation—the spectral overlap approach, the Marcus theory, and the Levich–Jortner theory—are compared for the calculation of charge carrier mobilities and exciton diffusion lengths for oligoacenes, using the master equation approach and Monte Carlo simulations. WIREs Comput Mol Sci 2016, 6:694–720. doi: 10.1002/wcms.1273 This article is categorized under: Structure and Mechanism > Computational Materials Science Abstract :